Cloning and expression of lactate dehydrogenase from plasmodium knowlesi for anti-malarial drug development - Ogu Salim, Nurhainis; Khairuddin, Farahayu; Jonet, Mohd Anuar; Ahmad Fuad, Fazia Adyani (2018)
Malaria remains a global burden, where drug resistance issue has triggered a major concern in the affected regions. Plasmodium lactate dehydrogenase, which is the key enzyme in the parasite‘s glycolytic pathway has shown to be a potential novel therapeutic target. The aim of the study is to clone and express the recombinant lactate dehydrogenase from Plasmodium knowlesi in bacterial system. Methods: The synthetic Pk-LDH gene was amplified and the PCR product with the size of 951bp was cloned into pET21a expression vector. The ligated product was transformed into BL21 (DE3) strain to induce Pk-LDH expression. Soluble expression was obtained at 20°C, incubated for 18 hours in Terrific Broth media in the presence of 0.5 mM isopropyl β-d-thiogalactoside (IPTG). The expressed Pk-LDH protein was later purified by using a combination of Immobilized Metal Affinity Chromatography (IMAC) and Size Exclusion Chromatography (SEC) methods. Sequencing and BLAST analysis revealed an open reading frame of 316 amino acids of Pk-LDH, which shows 91.8% sequence similarity with Plasmodium falciparum‘s LDH. The SDS–PAGE analysis exhibits that Pk-LDH protein of 34kDa in size was present in the soluble fraction. A sharp protein peak corresponding to the size of Pk-LDH was also observed upon gel filtration elution, indicating that the protein has successfully been purified to homogeneity. MALDI-TOF analysis gave a peptide score of 282, which is significant with L-lactate dehydrogenase from P. knowlesi, as revealed from the Mascot analysis. Pure and active Pk-LDH was obtained. Conclusions: The successful expression and purification system developed of Pk-LDH in this study offer a reliable method to produce soluble Pk-LDH that is biologically active, which can be used for future antimalarial drug development study.